EXPLORING THE ASSOCIATION BETWEEN NARCISSISTIC PERSONALITY DISORDER AND SOCIAL MEDIA USE - Imamović Lerić, Lejla; Husić, Indira (Srpski medicinski časopis Lekarske komore, 2024)
Introduction/Aim: Narcissistic personality disorder has become more and more noticeable in modern times. For an increasing number of people, their ego has become a springboard in society or an obstacle to their progress. The question is whether and to what extent narcissistic personality disorder is related to the use of social media networks. For young and older people alike, social media networks have become a part of everyday life. Social media networks are used in an attempt to show a reflection of everyday life that often represents a non-existent illusion. Therefore, social media networks present a false image, a fake splendor, in an attempt to show what is not there, so as to impress other people and induce them to think that the author of the content is somehow better or more important, i.e., more successful than them. This study attempts to link narcissistic personality disorder and the use of social media networks, in order to determine whether these two variables are related.Materials and methods: The basic research methods applied in this study are the method of analysis and synthesis, the method of induction and deduction, and the statistical and comparative methods. A total of 58 university students participated in the data collection process. The Narcissistic Personality Inventory and the Statements of Social Networking Usage Questionnaire (i.e., an inventory of social media presence and its purpose – academic, socialization, entertainment, information, compulsive use) were used in the study. Questions of a general nature (for collecting socio-demographic data) were also included. The study was conducted in Slovenia and Bosnia and Herzegovina, from January to June 2024.Results: A very low degree of correlation was found between narcissism and the academic purpose of using social media networks (0.20). A moderately strong correlation was found between narcissism and socialization as the purpose of using social media networks (0.663). A very weak correlation was found between narcissism and the informative purpose of using social media networks, more precisely, the correlation coefficient was 0.280. Finally, a high level of correlation was found between narcissism and entertainment as the purpose of using social media networks – the degree of correlation between these two variables was 88.8%.Conclusion: The research results indicate the existence of a significant relationship between narcissistic personality disorder and presence on social media networks.
Keywords: narcissism; disorder; social media networks; university students